A water-soluble magnesium sulfate bonded sand core material for manufacturing hollow composite castings. (1st October 2018) - Liu, Fuchu; Jiang, Peng; Huang, Ying; Jiang, Wenming; Liu, Xinwang; Fan, Zitian
Abstract: A high-strength and water-soluble magnesium sulfate bonded sand core (WSMBS) material cured by twice microwave heating was successfully fabricated using magnesium sulfate aqueous solution as a binder, which is suitable for manufacturing hollow composite structures castings. The effects of various factors on the properties of WSMBS were investigated. The results shows that WSMBS possesses some advantages of good water solubility, high curing speed and strength. The tensile strength of WSMBS is more than 0.6 MPa under optimal parameters, and when the temperature of WSMBS ranges from 105 °C to 116 °C, the tensile strength is superior and MgSO4 ·7H2 O is dehydrated to MgSO4 ·4H2 O or MgSO4 ·3H2 O. The moisture absorbability of WSMBS is quite high, and it rises with increasing the stored time and the magnesium sulfate binder content. The scanning electron microscope analysis shows that there are some micro-cracks or holes in the bonding bridge that decreases the strength of WSMBS after being put in humidistat for several hours. The energy dispersive X-ray analysis shows that the bonding bridge mainly comprises magnesium sulfate and so the use of WSMBS in casting does not release toxic gases. The water-solubility rate of WSMBS is 57.9 kg·min −1 ·m −2, which can be dissolved in water quickly after casting and overcome the poor leachability of the common bonded sand core, and therefore the used WSMBS can be easily reclaimed by water scrubbing method and the use of WSMBS can improve the production efficiency of the complex hollow composite castings with many interior channels or passages, undercuts. What is more, the aqueous solution of magnesium sulfate can be made from waste water which is used for dissolving the sand core after casting, and therefore it can realize green casting with no toxic gas during casting and recycling magnesium sulfate binder.